2019
DOI: 10.1002/cti2.1066
|View full text |Cite|
|
Sign up to set email alerts
|

Novel differential linear B‐cell epitopes to identify Zika and dengue virus infections in patients

Abstract: Objectives Recent Zika virus (ZIKV) outbreaks challenged existing laboratory diagnostic standards, especially for serology‐based methods. Because of the genetic and structural similarity of ZIKV with other flaviviruses, this results in cross‐reactive antibodies, which confounds serological interpretations. Methods Plasma from Singapore ZIKV patients was screened longitudinally for antibody responses and neutralising capacities against ZIKV. Samples from healthy controls, ZIKV patients and DENV patients were fu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 58 publications
1
10
0
Order By: Relevance
“…Similar analyses have already been performed in other works, where linear B-cell epitopes were employed for serological detection of several pathogenic organisms, such as Borrelia miyamotoiis (Tokarz et al, 2019), Toxoplasma gondii (Gatkowska et al, 2019), Treponema pallidum (Ogden et al, 2019), Leishmania spp. (Bremer Hinckel et al, 2019;Vale et al, 2019), and several human viruses (Amrun et al, 2019;Mutsvunguma et al, 2019;Yao et al, 2019). This reinforces the importance of these analyses, demonstrating the applications of linear B-cell epitopes in the diagnosis of human pathogenic organisms.…”
Section: Discussionsupporting
confidence: 66%
“…Similar analyses have already been performed in other works, where linear B-cell epitopes were employed for serological detection of several pathogenic organisms, such as Borrelia miyamotoiis (Tokarz et al, 2019), Toxoplasma gondii (Gatkowska et al, 2019), Treponema pallidum (Ogden et al, 2019), Leishmania spp. (Bremer Hinckel et al, 2019;Vale et al, 2019), and several human viruses (Amrun et al, 2019;Mutsvunguma et al, 2019;Yao et al, 2019). This reinforces the importance of these analyses, demonstrating the applications of linear B-cell epitopes in the diagnosis of human pathogenic organisms.…”
Section: Discussionsupporting
confidence: 66%
“…Pep10 and Pep12 from the JEV capsid protein also show increased cross-detection with antibodies from JEV and DENV1 patients, probably by acting as group-specific antigens (Huang et al, 1996). Peptides from the prM protein (such as Pep14, Pep15, Pep19, Pep20, Pep24, and Pep26) and from the envelope protein (such as Pep29, Pep30, and Pep86 of the DENV and ZIKV) also exhibit cross-detection with antibodies and may act as pan-flavivirus antigens (Amrun et al, 2019;Kam et al, 2019). Similarly, two linear peptides from the prM protein of the WNV (Pep27 and Pep28) were found to show similar cross-detection signals with anti-WNV and anti-JEV from convalescent patient sera (Gangwar et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…A mapping study based on prM protein identified linear reactive peptides from DENV3 and ZIKV using IgG serum samples from convalescent DENV and ZIKV patients (Amrun et al, 2019). Among the reactive peptides, one linear peptide from DENV3 and one from the ZIKV (Pep20, HITEVEPEDID CWCNLT; and Pep24, LDEGVEPDDVDCWCNTT) that reacted with both anti-ZIKV and anti-DENV antibodies were identified as potential common flavivirus-reactive antigens.…”
Section: Pre-membrane Proteinmentioning
confidence: 99%
See 2 more Smart Citations